2020
DOI: 10.3126/qjmss.v2i1.29023
|View full text |Cite
|
Sign up to set email alerts
|

Bankers' Communication Know-how: An Analysis from Commercial Banks of Kathmandu valley

Abstract: Background: In the modern era, communication has changed the way of working styles, banking sectors are practicing banking communication in order to make work easier, faster, comfortable and accurate. Banking communication plays the role of mediator in between bank, customer, government, shareholder, suppliers, client, board of directors and employees which strengthen connection between them. Therefore, banker's experience on banking communication enhances banking system, employee's behavior and core banking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…There are many financial institutions but we selected only 27 commercial banks in Nepal. The Kathmandu valley was a suitable area for research because it has a the largest population of in Nepal and the majority of banks headquarters and branches are located in the valley [14]. As highlighted before the study was conducted in the Kathmandu valley of Nepal.…”
Section: A Study Area and Populationmentioning
confidence: 99%
“…There are many financial institutions but we selected only 27 commercial banks in Nepal. The Kathmandu valley was a suitable area for research because it has a the largest population of in Nepal and the majority of banks headquarters and branches are located in the valley [14]. As highlighted before the study was conducted in the Kathmandu valley of Nepal.…”
Section: A Study Area and Populationmentioning
confidence: 99%
“…These strategies are: integrating, competing, avoiding, compromising, and accommodating. Nepal still has to reach the level of maturity and articulation on the scope of the negotiation (Paudel et al, 2020;Parajuli et al, 2020;Shrestha et al, 2020;Paudel et al, 2021;Paudel & Devkota, 2022). With so many new developments in trade and commerce, fierce competition, and very little knowledge of the subject, one can only imagine what our negotiators are going to do.…”
Section: Open Accessmentioning
confidence: 99%
“…Good communication skills should be given high priority in Nepalese organizations (Paudel et al, 2020). Effective communication skills can encourage more effective business practices and enable people within the company to communicate easily with each other (Parajuli et al, 2020;Shrestha et al, 2020). Thus, though several separate studies have been conducted in the areas of conflict, negotiation, and communication in the Nepalese market the study of the managerial role in conflict management and negotiation in the banking sector of Nepal is a noble area in Nepal.…”
Section: Open Accessmentioning
confidence: 99%
“…Thus, to establish effective communication, the manager has to channel the receiver what they mean to communicate in a precise, simple and direct way. Also, Shrestha et al (2020) revealed that only 37% employees of banks are adequately aware about banking communication thus, banks should implement effective strategy which could enhance employees' awareness on banking communication in context of Nepal.…”
Section: 113mentioning
confidence: 99%